Effective and robust rocking centrifugal pendulum vibration absorbers. (9th June 2022) - Mayet, Johannes; Acar, Mustafa A.; Shaw, Steven W.
Abstract: In this work, a design methodology for robust and effective centrifugal pendulum absorbers is presented with a relative center of mass translation along a given path and angular body rotation. This type of absorber is used in rotatory machines with rotor angle synchronous excitation, allowing for a reduction of angular rotor fluctuations over the entire speed range. The main areas of application are aircraft drives and automotive drive trains with internal combustion engines. Since the requirements placed on absorbers are increasingly demanding in terms of reducing their mass without sacrificing effectiveness, new design approaches must be pursued. The linear theory used in the past has been replaced by the nonlinear tautochronic design philosophy that provides an increased working range of the pendula. This approach has been extended in recent years with regard to nonlinear detuning in order to obtain effective and robust absorbers. It is known that, in addition to the translation of the pendula, the rotation of the pendulum bodies, contributes to absorber performance, and the nonlinear design tools are extended to this case. The proposed unified design approach allows one to apply existing tuning methodologies of centrifugal pendulum absorbers with their relative rotational movement, referred to as "rocking" absorbers. Maintaining generality, the equations of motion are derived for a system with multiple absorbers and prepared for the application of simulations and continuation algorithms for parameter studies. Additionally, a state transformation is presented, which allows the application of perturbation methods and averaging under the assumption of small parameters. The increased effectiveness of these rocking absorber class when compared to non-rocking absorbers is quantified and demonstrated by numerical case studies. Highlights: Nonlinear dynamics of rocking centrifugal vibration absorbers. Framework for tautochronic and nonlinear detuned absorbers. Analytical solutions of special rocking absorbers. Complete and consistent incorporation of roller dynamics, including their kinematic cutout contours.